Does the corporate financing behaviour of shariah compliant firms differ from non-shariah compliant firms? An Indonesian empirical evidence - Haron, Razali; Yusoff, Sheila Ainon (2016)
The substantial influence of Islamic Finance worldwide cannot be neglected with the encouraging potential and growth of Shariah compliant firms especially in Muslim dominated nations. Dual financing systems coexist in harmony between Islamic Finance and conventional thus motivates this study to examine and compare the determining factors of both types of firms’ financing decisions. By using three different regression techniques, the Pooled Ordinary Least Square (OLS), the Fixed Effects and the Random Effects, we analyse the impact of firm level and industry level determinants on corporate financing of the 290 Shariah compliant and 111 non-Shariah compliant firms in Indonesia. This study found that both the Shariah compliant and the non-Shariah compliant firms consider different determining factors in deciding their financing choices. The difference in the determining factors is most likely due to the different principles governing the two types of firms. The Shariah firms are deemed to adhere to the Shariah principles in running their operations and investments. This study has policy implication as it can assist those responsible to understand further the nature of both types of firms especially in the development of Islamic Finance to make Shariah compliant firms to flourish further with more innovative Islamic financing products to suit the needs.